Analysis of the Influence of Accountability and Transparency of the Personal Wealth of the Aceh People's Representative Council Through E-LHKPN on the Trust of the Acehnese People - Wirendra, Indah Putri; Lutfi, Achmad (Journal Public Policy, 2024)
This study examines the impact of accountability and transparency of personal wealth reporting by the Aceh People's Representative Council (DPRA) through e-LHKPN on the trust of the Acehnese people. The investigation is motivated by the high number of corruption cases in Aceh, with 13 cases in 2021 resulting in losses of IDR 25,994,129,987, which increased to 27 cases by April 2022. Transparency through the State Officials' Wealth Report (LHKPN) is crucial to mitigating corruption, yet the DPRA demonstrates the lowest compliance rate among regional institutions. Employing a mixed-method design, the study combines primary data from interviews with DPRA representatives and questionnaire responses from 120 Acehnese voters. The theoretical framework is based on Edward III’s inhibiting factors for policy implementation, and the data are analyzed using multiple linear regression. Findings reveal significant communication, resource, disposition, and bureaucratic structure issues hindering the effective implementation of the LHKPN policy. Accountability and transparency through e-LHKPN significantly influence public trust, explaining 77.7% of the trust variance (p < 0.05). While the bureaucratic structure is generally effective, inconsistent communication, technical challenges, and weak punitive measures for non-compliance undermine policy adherence. These findings underscore the need for enhanced communication, resource allocation, and enforcement mechanisms to improve accountability and transparency, thereby fostering greater public trust in the DPRA.